Hypopharyngeal Squamous Cell Carcinoma and Laryngeal Neuroendocrine Carcinoma Colliding in the Aryepiglottic Fold: A Case Report. (November 2017) - Marangoni, Roberta; Mauramati, Simone; Bertino, Giulia; Occhini, Antonio; Benazzo, Marco; Morbini, Patrizia
Purpose: A collision tumor consists of 2 different histologically distinct and topographically independent tumors merging in the same mass. In the head and neck region they are rare, with only 4 cases reported in the larynx. Case report: A 60-year-old heavy smoker complained of a left submandibular lesion in October 2014. The lesion was excised and showed a poorly differentiated carcinoma, suggestive for adenocarcinoma. After a positron emission tomography-computed tomography scan showed increased metabolic activity in the left laterocervical region and right vocal cord, the patient underwent endoscopic biopsy of the lesion of the left piriform sinus, which was positive for moderately differentiated squamous cell carcinoma (SCC). He was then submitted to circular pharyngolaryngectomy, reconstruction with a radial forearm free flap, and bilateral neck dissection. The histopathologic examination showed an in situ and microinvasive SCC of the left pyriform sinus colliding with a high-grade, non-small-cell neuroendocrine carcinoma of the larynx. Conclusions: To our knowledge, this is the first case described of laryngeal collision tumor comprising a neuroendocrine component. The choice of treatment of this kind of lesion is difficult because of the presence of 2 different histologies and of the controversial prognostic correlation of non-small-cell neuroendocrine neoplasms of the head and neck region.